Ideals of European Public Sphere and EU Journalism - Mörä, Tuomo (Sociologija. Mintis ir veiksmas, 2015)
Transnationalization of European politics and governance clearly causes challenges to the relations between political action, citizens and journalism. This article approaches these challenges by comparing the normative ideals of a public sphere to the conventions of contemporary journalism of the European Union. It seems that the ideals of public sphere, features of the EU’s executive character and media logics do not fit well with each other.